Genomic resources for the spotted ragged-tooth shark Carcharias taurus. Issue 1 (2nd January 2019) - Klein, JD; Bester-van der Merwe, AE; Dicken, ML; Emami-Khoyi, A; Mmonwa, KL; Teske, PR
Abstract : Genomic data can be a useful tool in the management and conservation of biodiversity. Here, we report the development of genomic resources for the spotted ragged-tooth shark Carcharias taurus using genome-wide DNA data from Illumina next-generation sequencing. We explored two commonly used genetic marker types: microsatellites and mitochondrial DNA. A total of 4 394 putative microsatellites were identified, of which 10 were tested on 24 individuals and found to have ideal properties for population genetic analyses. Additionally, we reconstructed the first complete mitochondrial genome of a South African spotted ragged-tooth shark, and highlight the most informative gene regions to facilitate future primer design. The data reported here may serve as a resource for future studies and can ultimately be applied in the sustainable conservation and fisheries management of this apex predator.